2021
DOI: 10.1111/ner.13398
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Dorsal Root Ganglion Stimulation in an Experimental Model of Painful Diabetic Peripheral Neuropathy: A Quantitative Immunocytochemical Analysis of Intracellular γ-Aminobutyric Acid in Dorsal Root Ganglion Neurons

Abstract: Background and Objective The sensory cell somata in the DRG contain all equipment necessary for extensive GABAergic signaling and are able to release GABA upon depolarization. With this study, we hypothesize that pain relief induced by conventional dorsal root ganglion stimulation (Con‐DRGS) in animals with experimental painful diabetic peripheral neuropathy is related to the release of GABA from DRG neurons. With use of quantitative immunocytochemistry, we hypothesize DRGS to result in a decreased intensity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Finally, the current was maintained in 0.5 mA and the frequency was lowered to 3 Hz (experiment #4), which gave rise to a positive effect on axonal growth, showing an increased axonal extension and axonal sprouting for the electrically stimulated DRG, compared with the non-stimulated ones. Several studies of neurostimulation of DRG have observed that low frequencies (<20 Hz) have a beneficial effect on pain relief, inducing the dorsal horn of the spinal cord inhibition via the activation of low threshold mechanoreceptors and the release of endorphins and dynorphins [ 76 , 77 , 78 , 79 ]. Therefore, we could say that the applied stimulation frequency of 3 Hz is within the physiological range of DRG activation.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the current was maintained in 0.5 mA and the frequency was lowered to 3 Hz (experiment #4), which gave rise to a positive effect on axonal growth, showing an increased axonal extension and axonal sprouting for the electrically stimulated DRG, compared with the non-stimulated ones. Several studies of neurostimulation of DRG have observed that low frequencies (<20 Hz) have a beneficial effect on pain relief, inducing the dorsal horn of the spinal cord inhibition via the activation of low threshold mechanoreceptors and the release of endorphins and dynorphins [ 76 , 77 , 78 , 79 ]. Therefore, we could say that the applied stimulation frequency of 3 Hz is within the physiological range of DRG activation.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by our calcium imaging results indicating that Narirutin presents disparate effects on four types of neurons, we hypothesis that Na v 1.7 expression in different types of neurons after SNI is varied. Since the small-diameter neurons are mainly C-fiber-related nociceptors [ 38 , 39 ], we conducted immunostaining CGRP and IB4 for labeling unmyelinated peptidergic or non-peptidergic sensory neurons, and NF200 for myelinated neurons [ 40 ]. Calcitonin gene-related peptide (CGRP), a 37 amino-acid neuropeptide found mostly in peptidergic sensory C-fibers, has been suggested to be implicated in the pathogenesis of neuropathic pain [ 41 ], which is likely mediated by modulating nociception and sustaining neurogenic inflammation that leads to further peripheral and central pain sensitization [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 There is evidence indicating that the DRG can be a relevant target for analgesic treatment in the experimental animal models. 5 , 6 More recent studies on the experimental model of painful diabetic peripheral neuropathy in rats confirmed a generally positive effect on animal pain-related behavior using conventional 7 , 8 and burst DRG stimulation. Furthermore, a similar effect was obtained for experimental animal models of osteoarthritis 10 and rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 86%
“…Experimental animal studies preceding clinical studies or performed in parallel with them can enhance the understanding of the effect of electrical stimulation on injured DRGs. However, a systematic review of the literature revealed only six publications that have analyzed DRG stimulation in experimental pain models 8 , 9 , 24–27 and two more that investigated the stimulation effect in healthy animals. 28 , 29 In all these cases, the pathophysiological mechanisms behind DRG stimulation still remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%